The iron cage of the music teaching profession: A multi-case study on how primary music teachers in Spain understand bureaucracy - Mateos-Moreno, Daniel; Bravo Fuentes, Paloma (Sage Journals, 2023)
Despite being an unavoidable part of the music teaching profession, bureaucracy remains an understudied and ill-defined topic in the research literature. However, its investigation may benefit the music teaching profession by re-thinking policy, informing music teacher education programmes and fostering a mutual understanding among music teachers and policymakers. Therefore, in the present study, we aimed to investigate the understandings of Spanish music teachers in relation to bureaucracy and to compare these with the views of the teachers of other subjects in primary education. The perspective of purposefully selected music teachers were thus explored in-depth and contrasted with the views of their counterparts in a multiple case-study design. Our findings contribute a taxonomy of bureaucracy in the music teaching profession. Additionally, we conclude that the views of our music teacher participants on bureaucracy are mainly negative and slightly more pessimistic than those of their counterparts. In discussing our results, we connect these views with the Weberian ‘iron cage’ of bureaucracy and Arendt’s ‘government of Nobody’ as a substitute for democracy in governing education. Finally, we hypothesise a dystopic future of deprofessionalisation as a result of these primary music teachers’ declared lack of control over their own organisational tasks.
Keywords: Música - Estudio y enseñanza; Bureaucracy; Education; Music; Profession; Teacher